Process Study on Curing Composite Material T-Stiffened Panel - Peng, W.F.; Zhan, L.H.; Zeng, L.R.; Bai, H.M. (Asian Journal of Chemistry, 2014)
Stiffened composite panels are the main structure of aerospace bearing components. Furthermore, the forming quality of the R region is important yet difficult. This paper focused on the research of the temperature and curing degree of the R region of a co-curing stiffened panel. By using finite element analysis, this paper builds an FE model with thermal-chemical coupling and analyzes the temperature field distribution of a cross-section and the curing degree field distribution of a composite. The FE model investigates the co-curing of a longitudinal section of a T-stiffened panel. Through point tracking, the heating rate’s effect, the curing process temperature on the resin curing temperature, the curing degree and the curing rate are determined. The results lay a theoretical foundation for further research over the forming quality of the R region.